2019
DOI: 10.3892/mmr.2019.9940
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized unsaturated fatty acids induce apoptotic cell death in cultured cells

Abstract: Polyunsaturated fatty acids are oxidized by non-enzymatic or enzymatic reactions. The oxidized products are multifunctional. In this study, we investigated how oxidized fatty acids inhibit cell proliferation in cultured cells. We used polyunsaturated and saturated fatty acids, docosahexaenoic acid (DHA; 22:6), eicosapentaenoic acid (EPA; 20:5), linoleic acid (LA; 18:2), and palmitic acid (16:0). Oxidized fatty acids were produced by autoxidation of fatty acids for 2 days in the presence of a gas mixture (20% O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 46 publications
3
16
0
Order By: Relevance
“…Pasini et al found elevated lysophosphotidylcholine in the plasma of smokers vs never-smokers and that exposure to oxidised lipids increased the level of lysophosphotidylcholine in never-smoker PBMCs 78 . Oxidised lipids are also known to induce apoptosis in cells 79 , 80 and in this study we showed that CS-oxidised lipids were able to induce bronchial epithelial cell necrosis and apoptosis. Thus, the authors suggest that smoking results in increased lysophosphotidylcholine and oxidised lipids in the airways from apoptotic epithelial cells which in turn may trigger further apoptosis of cells in the airways as well as inflammation, contributing to a vicious cycle of ongoing airway cell apoptosis even after smoking may have ceased, something that is documented to occur in COPD ex-smoker patients 12 , 77 .…”
Section: Discussionsupporting
confidence: 56%
“…Pasini et al found elevated lysophosphotidylcholine in the plasma of smokers vs never-smokers and that exposure to oxidised lipids increased the level of lysophosphotidylcholine in never-smoker PBMCs 78 . Oxidised lipids are also known to induce apoptosis in cells 79 , 80 and in this study we showed that CS-oxidised lipids were able to induce bronchial epithelial cell necrosis and apoptosis. Thus, the authors suggest that smoking results in increased lysophosphotidylcholine and oxidised lipids in the airways from apoptotic epithelial cells which in turn may trigger further apoptosis of cells in the airways as well as inflammation, contributing to a vicious cycle of ongoing airway cell apoptosis even after smoking may have ceased, something that is documented to occur in COPD ex-smoker patients 12 , 77 .…”
Section: Discussionsupporting
confidence: 56%
“…It was even reported that there is a differential role of saturated and unsaturated fatty acids, whereas unsaturated fatty acids influence autophagy but do not promote apoptosis, saturated fatty acids suppress autophagy and induce apoptosis [39]. However, other studies found that unsaturated lipids can induce apoptotic cell death, especially when peroxidized [40,41]. We conclude that the observed changes in lipid composition caused by disruption of lysosomal function lead to a change in mitochondrial membrane composition, which on the one hand impairs mitochondrial function and on the other, triggers release of cytochrome C to the cytosol and subsequently induces apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Unsaturated bonds in the hydrocarbon chains of phosphatidylethanolamine are susceptible to ROS-mediated oxidation (Iuchi et al, 2019). The process is tightly connected with ferroptosis -a type of cell death, induced by the accumulation of lipid peroxides in the membrane (Conrad et al, 2018).…”
Section: Phosphatidylethanolamine (Pe)mentioning
confidence: 99%